(−)-Nyasol, isolated from Anemarrhena asphodeloides suppresses neuroinflammatory response through the inhibition of I-κBα degradation in LPS-stimulated BV-2 microglial cells. (October 2013) - Lee, Hwa Jin; Li, Hua; Chang, Hee Ryun; Jung, Hyeyoun; Lee, Da Yeon; Ryu, Jae-Ha
Abstract : Microglial activation has been associated with neurodegenerative diseases by inducing the neuroinflammatory mediators such as nitric oxide (NO), TNF-α and IL-1β. (−)-Nyasol, a norlignan isolated from a medicinal plant Anemarrhena asphodeloides, showed anti-inflammatory potential in lipopolysaccharide (LPS)-activated BV-2 microglial cells. (−)-Nyasol inhibited the production of NO and prostaglandin E2 (PGE2 ) and also the expression of inducible nitric oxide synthase and cyclooxygenase-2, which are responsible for the respective production of NO and PGE2 . It also suppressed the mRNA levels of TNF-α and IL-1β in activated microglial cells. These effects of (−)-nyasol were correlated with the inactivation of p38 MAPK and the suppression of LPS-induced I-κBα degradation. Taken together, these results suggest that (−)-nyasol can be a modulator in neuroinflammatory conditions induced by microglial activation.